KIF11 silencing and inhibition induces chromosome instability that may contribute to cancer. Issue 9 (15th June 2017) - Asbaghi, Yasamin; Thompson, Laura L.; Lichtensztejn, Zelda; McManus, Kirk J.
Abstract: Understanding the aberrant pathways that contribute to oncogenesis and identifying the altered genes involved in these pathways is a critical first step to develop effective strategies to better combat cancer. Chromosome instability (CIN) is an aberrant phenotype that occurs in ∼80% of all cancer types and is associated with aggressive tumors, the acquisition of multidrug resistance and poor patient prognosis. Despite these associations however, the aberrant genes and molecular defects underlying CIN remain poorly understood. KIF11 is an evolutionarily conserved microtubule motor protein that functions in centrosome and chromosome dynamics in mitosis. Interestingly, the yeast ortholog of KIF11, namely CIN8 is a CIN gene and thus aberrant KIF11 expression and function is suspected to underlie CIN. In support of this possibility, KIF11 is somatically altered in a large number of cancer types. Using a complementary biochemical and genetic approach we examined whether KIF11 silencing with siRNAs or inhibition with monastrol was able to convert two distinct and karyotypically stable cell lines into karyotypically unstable cell lines. Indeed, quantitative imaging microscopy and flow cytometry revealed that KIF11 silencing induced increases in nuclear areas, micronucleus formation, DNA content and chromosome numbers relative to controls that was also observed following KIF11 inhibition. Collectively, this study identifies and validates KIF11 as an evolutionarily conserved CIN gene, and further suggests that aberrant expression and function may contribute to the pathogenesis of a subset of cancers.